The prevalence of deafness-associated mutations in neonates: A meta-analysis of clinical trials. (June 2019) - Chen, Shuilian; Liang, Zhijiang; Chen, Baoxin; Yao, Fei; Huang, Guanhao; Zhu, Juan; Li, Yuping; Gao, Shuang; Zhao, Qingguo
Abstract: Objective: The causative genes associated with autosomal recessive non-syndromic hearing loss (ARNSHL) have been identified, in order of prevalence are GJB2, SLC26A4, MYO15A, OTOF, CDH23, and TMC1 . To evaluate the prevalence of deafness-associated mutations in neonates and the clinical value of screening, we performed a meta-analysis of clinical trials. Methods: The main criteria used to select articles was that the studies were designed to detect deafness genetic mutations in Chinese's neonates, and the screening kits were designed to detect 9 or 20 sites in four deafness-causative genes. The combined effect of genetic screening was measured by the pooled prevalence of mutations with 95% confidence intervals (CIs). The Random Model was used to estimate the pooled prevalence of mutations. Results: We included 18 studies (a total of 261766 neonates) from studies using 9-mutation screening kit, and 15 studies (a total of 131158 neonates) from studies using the 20-mutation screening kit to conduct meta-analysis. The Random Model was used to estimate the pooled prevalence of mutations due to large heterogeneity (9 sites: I 2  = 89.1%, P = 0.0000; 20 sites: I 2  = 97.3%, P = 0.0002). The pooled prevalence of mutations in 9 sites group was 0.043 (95%CI:0.039–0.047, Z = 21.49, P = 0.000)and 20 sites group was 0.047(95%CI:0.041–0.053, Z = 15.84, P = 0.000). Conclusions: The prevalence of deafness-associated mutations in neonates in China is 4.7%; Based on the current detection technology and deafness genetics knowledge, it may be more reasonable to offer 1494C > T and 1555A > G mutation screening to pregnant women. Decision makers should think about how to use the current deafness genetic screening to amplify the effectiveness of hearing screening.